Policy Networks and Good Governance A Discussion - Thompson, Graham; Pforr, Christof (2005)
Policy network research can be divided, broadly, into two schools of thought:the interest intermediation school (policy networks as an analytical tool) and the governance school (policy networks as a form of governance). Both schools have made significant contributions towards raising our awareness about policy networks through the development of concepts, theories and research methods. While acknowledging these achievements contemporary literature suggests that this research has been mainly descriptive, with few primary empirical studies being undertaken in particular to assess the effectiveness of policy networks. This paper reviews briefly the recent literature on policy networks. The literature review reveals that by combining and adapting the most relevant quantitative and qualitative research methods from previous studies, contributions can be made towards developing better standards for evaluating, and developing, the democratic quality of policy networks as a form of (good) governance.